KEANEKARAGAMAN FAUNA DI TAMAN KEANEKARAGAMAN HAYATI CILEGON PT. CHANDRA ASRI - Pipit Marianingsih; Mahrawi Mahrawi; Yopi Haryandi; Adira Cahyani; Riesta Octoviani; Syifa Nurrohmah; Laili Sabta Nugraha; Yoseph Sugiharto Karahayon; Eren Putra Febrio (LPPM Universitas Negeri Jakarta, 2023)
The establishment of Taman Kehati Asri by PT Chandra Asri is a form of protection of biodiversity to improve the quality of biodiversity, including fauna. The existence of fauna is very important in ecosystem activities because fauna is a consumer in the food pyramid. If a population decreases, it will have a negative impact on the continuity of food webs and hinder the flow of energy cycle. This study aimed to identify the diversity of fauna in the Taman Kehati Asri area of PT. Chandra Asri Petrochemical, in Gunung Sugih Village, Ciwandan District, Cilegon City, Banten. The research was conducted in October 2022. The methods used were point count and cruise method. Based on the research results, it was found that there were 37 species of fauna belonging to 4 classes, namely birds, mammals, herpetofauna and insects. The result of total species diversity index was 2.98 which was categorized as in the medium category. Furthermore, the fauna dominance index was 0.075 which indicated that one or several species of fauna were not dominated in that area.